The involvement of anti-inflammatory protein, Annexin A1, in ocular toxoplasmosis - Mimura, Kallyne K.; Tedesco, Roberto C.; Calabrese, Katia S.; Gil, Cristiane D.; Oliani, Sonia M. [UNESP] (My University, 2012)
Purpose: The aim of this study was to evaluate the expression of the protein annexin A1 (ANXA1), a potent endogenous regulator of the inflammatory process, in ocular toxoplasmosis. Methods: C57BL/6 female mice were infected using intravitreal injections of either 10 6 tachyzoites of Toxoplasma gondii (RH strain; T. gondii) or PBS only (control groups). After 24, 48, and 72 h, animals were sacrificed and their eyes were harvested for histopathological, immunohistochemical, and ultrastructural immunocytochemical analysis of ANXA1. Human retinal pigment epithelial (RPE) cells (ARPE-19) were infected in vitro with T. gondii and collected after 60, 120, 240 min, and 24 h. Results: Compared with non-infected eyes, an intense inflammatory response was observed in the anterior (24 h after infection) and posterior segments (72 h after infection) of the infected eye, characterized by neutrophil infiltration and by the presence of tachyzoites and their consequent destruction along with disorganization of normal retina architecture and RPE vacuolization. T. gondii infection was associated with a significant increase of ANXA1 expression in the neutrophils at 24, 48, and 72 h, and in the RPE at 48 and 72 h. In vitro studies confirmed an upregulation of ANXA1 levels in RPE cells, after 60 and 120 min of infection with T. gondii. Conclusions: The positive modulation of endogenous ANXA1 in the inflammatory and RPE cells during T. gondii infection suggests that this protein may serve as a therapeutic target in ocular toxoplasmosis. © 2012 Molecular Vision.
Keywords: lipocortin 1; animal cell; animal experiment; animal model; animal tissue; cell vacuole; controlled study; disease association; eye inflammation; female; in vitro study; mouse; neutrophil chemotaxis; nonhuman; pigment epithelium; priority journal; protein expression; retina; tachyzoite; Toxoplasma gondii; toxoplasmosis; upregulation; Animals; Annexin A1; Anterior Eye Segment; Epithelial Cells; Female; Gene Expression Regulation; Humans; Interferon-gamma; Intravitreal Injections; Mice; Mice, Inbred C57BL; Neutrophil Infiltration; Posterior Eye Segment; Retinal Pigment Epithelium; Toxoplasma; Toxoplasmosis, Animal; Toxoplasmosis, Ocular